Steady State Hydration Levels of Career Firefighters in a Large, Population-Based Sample. Issue 1 (January 2019) - Suminski, Richard R.; Poston, Walker S.C.; Day, Rena S.; Jitnarin, Nattinee; Haddock, Christopher K.; Jahnke, Sara A.; Dominick, Gregory M.
Abstract : Objectives: To establish the extent of steady state hypohydration among firefighters and examine factors associated with their hydration status. Methods: Data on 450 career firefighters from 11 randomly selected fire departments had their body composition, total body water (TBW), and hypohydration status assessed using bioelectrical impedance. Measured height and weight were used to determine body mass index (BMI) and weight classification. Results: The hypohydration rate was 17% and 94% of hypohydrated firefighters were obese. A one-unit increase in BMI was associated with an 83% greater likelihood of being hypohydrated. Conclusions: This study indicates that steady state hypohydration is a significant issue among obese firefighters. Current hydration policies based on previous reports that most (more than 90%) firefighters are hypohydrated in the steady state should be revisited and additional, confirmatory research in this area should be conducted.